Beyond the Classroom Factors Driving Learners to Kampung Inggris Pare - Muhammad Bambang Purwanto; Moch Malik Firdaus; Yusri Yusri; Sutarno Sutarno (Foreign Language Instruction Probe, 2025)
Kampung Inggris Pare has become Indonesia's largest English learning center, attracting thousands of learners from various regions with diverse backgrounds. However, the main factors that drive them to choose Kampung Inggris over other course institutions have not been thoroughly researched. This study analyzes these factors and identifies the dominant factors in learners' decisions. This study used a qualitative descriptive method with a case study approach, involving 40 learners as research subjects. Data were collected through questionnaires, interviews, and observations, then analyzed using quantitative and qualitative descriptive approaches. The results show that intensive learning methods, a supportive environment, and affordable costs are the main factors that attract learners. The conclusion of this study confirms that Kampung Inggris has unique advantages that are difficult to find in other course institutions.